2016
DOI: 10.1158/1055-9965.epi-15-0225
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts an Advanced-Stage Diagnosis of Breast Cancer? Sorting Out the Influence of Method of Detection, Access to Care, and Biologic Factors

Abstract: Background: Multiple studies have yielded important findings regarding the determinants of an advanced-stage diagnosis of breast cancer. We seek to advance this line of inquiry through a broadened conceptual framework and accompanying statistical modeling strategy that recognize the dual importance of access-tocare and biologic factors on stage.Methods: The Centers for Disease Control and Preventionsponsored Breast and Prostate Cancer Data Quality and Patterns of Care Study yielded a seven-state, cancer regist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 71 publications
0
21
1
3
Order By: Relevance
“…25,26 Although some authors have associated younger age at diagnosis with later stage at presentation, 27 others have found the reverse. 14 We did not find an association between age at diagnosis and stage.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…25,26 Although some authors have associated younger age at diagnosis with later stage at presentation, 27 others have found the reverse. 14 We did not find an association between age at diagnosis and stage.…”
Section: Discussioncontrasting
confidence: 55%
“…38 In New Zealand, researchers have reported poorly differentiated tumour grade (II and III) in women with late stage disease, 16 similar to findings in the United States, by Lipscomb et al who found advanced stage breast cancer to be positively related with poorly differentiated tumour grade and HER2 type tumours. 14 Our sample size for this analysis was, however, very limited, and thus, the influence of tumour characteristics on stage at diagnosis still needs to be fully explored in the SSA setting. The majority of biopsies in our study were core needle biopsies whose results tend to differ from excisional biopsies perhaps due to under-sampling of a heterogeneous tumour and insufficient amount of tumour in the cores taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of tumor growth can be affected by biological determinants such as hormone receptor and/or environmental factors such hormone exposure during pregnancy. The likelihood of metastatic spread increases as cancers grow, meaning that delays to prompt diagnosis and treatment are associated with worsened prognosis, delays that can be attributed to both system‐ and woman‐level (lifestyle, sociodemographic) factors . In SSA, BC diagnosis typically concerns symptomatic disease, therefore the time interval between onset of symptoms and seeking help provides a critical time window of opportunity for achieving early diagnosis .…”
mentioning
confidence: 99%
“…Although significantly improved, the majority of cancer deaths are due to metastases, not due to the primary tumor. 4,5 No unifying theory exists for the human carcinogenesis, although many proposals exist. 6 To date, most mechanistic or pathway-level analyses have been experimental in vitro or animal studies.…”
mentioning
confidence: 99%